Linewidth broadening caused by intrinsic temperature fluctuations in quantum cascade lasers - Liu, T. (2013)
The intrinsic narrow linewidth of quantum cascade lasers (QCLs) promises wide applications such as highsensitive trace-gas detection. However, so far limited work has been reported in intrinsic linewidth characteristics of QCLs. In this paper, we theoretically investigate the linewidth broadening caused by intrinsic temperature fluctuations in both mid-infrared and Terahertz QCLs. When microscopic features of the refractive index variations associated with the intersubband transitions and energy level broadening in mid-infrared QCLs are considered, the linewidth broadening increases up to a few hundred Hz in mid-IR QCLs.